Diversity of Fusarium Link and mite species associated with malformed Syzygium cordatum Hochst. Ex Krauss (water berry) inflorescences - Fourie, Gerda (University of Pretoria, 2023)
Thesis (PhD (Plant Pathology))--University of Pretoria, 2023.